Skinfold thickness in elite male professional football players: changes across 3 seasons including a COVID-19 lockdown period - Flannigan, C.; Robinson, M.; Rodriguez-Sanchez, N.; Drust, B.; McGregor, R.; Galloway, S. (Science and Medicine in Football, 2024)
This study investigates variations in skinfold thickness in a European professional football team within and across multiple seasons, including before and after COVID-19 restrictions. Skinfold thickness was measured in 49 male players on 32 occasions across three seasons (2018/19, 2019/20 and 2020/21). Intra- and inter-seasonal trends were examined by comparing values for the sum of eight skinfolds (sum8) at key time points using linear mixed models. In each season, the largest differences in sum8 occurred after the preseason period. These differences ranged from a mean difference (Mdiff) of -11.0 mm (p < 0.001) in 2018/19 to -4.8 mm (p < 0.001) in 2020/21. Increases in sum8 occurred after each off-season; however, the increase after the off-season before the 2020/21 season (which included the COVID-19 lockdown period) was the lowest in magnitude and was not statistically significant (Mdiff = 2.9 mm, p = 0.06). Changes occurring in sum8 between the start and end of the competitive season did not follow a consistent pattern and were generally smaller in magnitude than the changes between other seasonal time points. Despite the notable heterogeneity in sum8 between players, changes within players generally followed a similar pattern between the different seasonal timepoints. In summary, changes in skinfold thickness were predominantly related to off-season and `preparation for competition` periods. Increases in skinfold thickness can be mitigated during extended remote training periods with appropriate training and nutritional strategies.